Corporate Social Responsibility sebagai Daya Tarik Organisasi bagi Calon Karyawan - Pasaribu, Saddam Azhar; Darmadi, Didi; Ludfi Arifin, Antoni; Azmy, Ahmad (Journal of Management and Bussines (JOMB), 2024)
Corporate Social Responsibility (CSR) has become an essential element in attracting prospective employees in the modern era. This study aims to understand how CSR practices influence the decisions of job candidates in selecting an organization as a place of work. The results show that strong CSR programs can significantly contribute to enhancing the organization's reputation, especially in the eyes of individuals whose values align with the company's social vision. CSR is seen not only as a marketing tool but also as a tangible expression of the organization's commitment to social and environmental sustainability. These findings suggest that prospective employees are more attracted to companies that demonstrate consistent and relevant social responsibility. Therefore, this study offers valuable insights for organizations in designing effective CSR strategies to strengthen their appeal in the labor market. With the increasing awareness of the importance of sustainability, CSR can serve as a strategic tool to attract top talent while building stronger relationships with potential employees. This research uses a literature study method by analyzing various relevant scholarly references to explore the role of CSR as an organizational attraction and the company's reputation in the eyes of prospective employees. The findings indicate that good CSR policies can enhance the company's image as an ethical, attractive, and sustainability-oriented organization. Keywords : Corporate Social Responsibility, Prospective Employees, Organizational Attractiveness, Corporate Reputation